The Supportive Role of NSC328382, a P2X7R Antagonist, in Enhancing the Inhibitory Effect of CRID3 on NLRP3 Inflammasome Activation in Rats with Dextran Sodium Sulfate-Induced Colitis - Saber S; Yahya G; Gobba NA; Sharaf H; Alshaman R; Alattar A; Amin NA; El-Shedody R; Aboutouk FH; Abd El-Galeel Y; El-Hefnawy A; Shabaka D; et al. (Dove Medical Press, 2021)
Sameh Saber,1 Galal Yahya,2 Naglaa A Gobba,3 Hossam Sharaf,4 Reem Alshaman,5 Abdullah Alattar,5 Noha A Amin,6 Ruwyda El-Shedody,4 Farah H Aboutouk,4 Yumna Abd El-Galeel,4 Amr El-Hefnawy,4 Dina Shabaka,4 Arwa Khalifa,4 Renad Saleh,4 Donya Osama,4 Ghada El-Zoghby,4 Mahmoud E Youssef1 1Department of Pharmacology, Faculty of Pharmacy, Delta University for Science and Technology, Gamasa, Egypt; 2Department of Microbiology and Immunology, Faculty of Pharmacy, Zagazig University, Al Sharqia, Egypt; 3Department of Pharmacology and Toxicology, College of Pharmacy, Misr University for Science and Technology, Cairo, Egypt; 4Department of Clinical Pharmacy, Faculty of Pharmacy, Delta University for Science and Technology, Gamasa, Egypt; 5Department of Pharmacology and Toxicology, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 6Department of Haematology, Theodor Bilharz Research Institute, Giza, EgyptCorrespondence: Mahmoud E Youssef; Sameh SaberDepartment of Pharmacology, Faculty of Pharmacy, ‎Delta University for Science and Technology, Costal International Road, P.O. Box: +11152, Mansoura, Dakahlia, EgyptTel +2 50 2770140; +2 01033124949Fax +2 50 2770140Email mahmoodelsaid@hotmail.com; sampharm81@gmail.com; sameh.mohamed@deltauniv.edu.egPurpose: The NLRP3 inflammasome is a substantial component of the inflammation process. The complex pathogenesis of and the implication of a vast number of components in the inflammasome-activation pathway prompted us to search for compounds that have a wide therapeutic index and act at the level of multiple cellular targets. Although CRID3 blocks NLRP3 with high specificity in the laboratory, clinical trials of the compound reported weaker potency.Methods: We used NSC328382, a P2X7R antagonist, as an adjunctive therapy and generated a strategy to potentiate the effects of CRID3 in rats with DSS-induced colitis.Results: NSC328382/CRID3 combined therapy exhibited a significantly increased efficacy compared with either of the monotherapies. NSC328382/CRID3 was more efficient in 1) attenuating colon shortening and disease activity; 2) improving goblet cell density and both the macroscopic and microscopic scenario of the injured colon; 3) improving the antioxidant defense mechanisms of the inflamed colon against oxidative stress; and 4) mitigating the inflammation state by downregulating the proinflammatory cytokines. Pyroptotic cell death was also conspicuously restrained. Additionally, NSC328382 interrupted the MyD88/NF-κB axis. Moreover, NSC328382/CRID3 exhibited the ability to alter Th1/Th2 dominance.Conclusion: The clinical application of NSC328382/CRID3 may result in the generation of a novel approach for the treatment of IBDs.Keywords: NSC328382, CRID3, P2X7R/NLRP3, MyD88/NF-κB, Colitis